Typology Analyses and Strategic Stakeholders’ Mapping Using Network on Integrated Crops-Livestock Farming Systems - Deny Anjelus Iyai; I Widayati; H Fatem; D Nurhayati; M Arim; H Monim; H Mofu; A Baaka; M L Orisu; D T.R Saragih; Y Syufi; O Yoku; J Woran; W Y Mofu; S Y Randa; D Sawen; A R Ollong; M Baransano; D Seseray; A G Murwanto; A Yaku; D D Rahardjo (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
Stakeholders and their networks play prominent roles in developing the agricultural sector. For instance, the economic, social, and environmental indicators of farms are sustained by the involvement of stakeholders and other relevant parties. Therefore, exploring the importance and roles of actors has become strategic and vital to recognize. This research aims to determine the strategic stakeholders' typology and mapping using their network analyses on integrated crops-livestock farming systems in West New Guinea. The study was carried out in Manokwari using the focus group discussion on twenty various represented individuals, groups, and mass institutions. The queries discussed were based on background, resources delivery, inter-connectivity amongst actors, intervention, and innovation. The result showed that the stakeholders in mixed crop-livestock are dominated by individuals' that privately manage the farms officially in accordance with the laws. The result also showed that the farming systems in West New Guinea, experience real threats which need to be lowered to mitigate the turn-back effect. The top five shared resources are access, satisfaction, power, knowledge, and time allocation. These resources tend to stay longer to sustain the strong needs of the farms, which are dominated by positive similarity with varying ranges of correlation ranging from negative, neutral to positive. This is because the stakeholders are reluctant to deliver the intervention and innovation, therefore, those with low interest and power need to be promoted to high interest and power by using aids, guidance, and services from each actor in the mixed crop-livestock farms business.